Toward a Process-Transfer Model of the Endorser Effect. (June 2020) - Wong, Vincent Chi; Fock, Henry; Ho, Candy K.Y.
Previous research on the effects of celebrity endorsement has focused on the transfer of positive properties (likeableness, credibility, symbolic meanings, etc.) from the endorser to the product. Taking a different perspective, this study suggests that the way in which consumers evaluate an endorser (i.e., the cognitive process, such as applying family origin or achievement as the basis for evaluation) will carry over to the evaluation of the endorsed product (e.g., applying country of origin or performance as the criteria). Five experiments support this process-transfer account and show that it can be induced by subtle verbal/visual cues in advertisements. Because the process transfer is not inherently associated with positive/negative valence, it provides a theoretical rationale for explaining successful endorsements involving endorsers who are less favorable/credible, less of a "fit" with the product, or associated with some negative meanings, in addition to those involving positively or neutrally evaluated endorsers. The process-transfer model supplements existing models and provides a more comprehensive understanding of endorser effects. It provides marketers with a set of less stringent guidelines for selecting endorsers as well as valuable damage control tools for brands when an endorser screws up.